Point-of-care ultrasonography-assisted nasogastric tube placement in the emergency department: a randomized controlled trial. (14th July 2022) - Yaseen, Mohd; Kumar, Akshay; Bhoi, Sanjeev; Sinha, Tej Prakash; Jamshed, Nayer; Aggarwal, Praveen; Murmu, Lakhi Ram; Ekka, Meera
Abstract : Background: The complications of a blind procedure for gastric tube placement are well documented. POCUS has been widely used to confirm the position of blindly inserted gastric tubes, and it does not prevent complications caused by the blind method. We performed a randomized controlled trial to compare gastric tube insertion with real-time oesophagus visualization using POCUS to the standard technique. Objective: The primary goal of this study was to compare the accuracy of real-time POCUS-guided nasogastric tube (NGT) insertion and confirmation to that of the standard technique. Methods: It was a prospective, parallel-group, open-label randomized controlled trial with a superiority design. All patients requiring NGT were screened for inclusion and exclusion criteria, and 120 patients were randomly assigned to one of two groups: POCUS ( n = 60) or control ( n = 60). Following the procedures, confirmatory chest radiographs were obtained in both groups. Results: As per protocol, 118 patients were analyzed. In POCUS group, the oesophagus was visualized on POCUS in 56 of 58 patients (96.5%). In 55 of 58 cases (94.8%), an NGT was inserted in real time. Despite visualizing the oesophagus, we fail to insert the tube in one (1.8%). The oesophagus could not be seen on the scan in two cases (3.4%). Chest radiographs confirmed the tube in the stomach in 55 (98.2%). The chest radiograph revealed the tip of the NGT in the stomach in 52 of 60 (86.6%) patients. In seven cases (11.7%), we were unable to insert NGT. On a chest radiograph, one (1.6%) tip of the tube was seen in the right lung and was safely removed. The ultrasound-guided gastric tube insertion had a sensitivity of 96.5% (95% CI, 88–99.6%) and a positive predictive value (PPV) of 98.2% (95% CI, 98.1–98.3%). The conventional technique had 88% (95% CI, 77–95%) sensitivity and a PPV of 98% (95% CI, 97.9–98.2%). Conclusion: POCUS enables real-time insertion of a gastric tube with high sensitivity, in a short time with high first-attempt success rate and limited passage-related complications. POCUS should be utilized for NGT insertion whenever expertise is available on the bedside.